2006
DOI: 10.1093/bja/ael057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aminocaproic, tranexamic acids in the control of bleeding during total knee replacement: a randomized clinical trial

Abstract: Antifibrinolytic agents produce a significant decrease in blood loss in patients undergoing total knee replacement, reflected in a reduction in the number of blood transfusions required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
170
0
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(198 citation statements)
references
References 22 publications
12
170
0
16
Order By: Relevance
“…The sample size was calculated as follows. Camarasa et al reported the total blood loss after traditional total knee replacement in a control group was 1784 (660) mL [9]. Assuming a mean difference of 400 mL or greater total blood loss between two groups, to obtain a statistical power of 0.85 and alpha error of 0.05, 45 patients were required in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated as follows. Camarasa et al reported the total blood loss after traditional total knee replacement in a control group was 1784 (660) mL [9]. Assuming a mean difference of 400 mL or greater total blood loss between two groups, to obtain a statistical power of 0.85 and alpha error of 0.05, 45 patients were required in each group.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used successfully to reduce the blood loss in cardiac surgery [22], liver surgery [4], and gynecology [30]. The efficacy of tranexamic acid administered intravenously in preventing blood loss in TKA has been established in numerous studies [2,6,[12][13][14][15]29]. Topical application of tranexamic acid intraoperatively has shown a decrease in blood loss after TKA without the disadvantage of systemic absorption and thromboembolic complications [31].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review shows studies where tranexamic acid was administered either as a single dose just before the release of the tourniquet [1,13] or along with an additional postoperative dose [2,6,12,14,32]. Inflation of the tourniquet stimulates the fibrinolytic system; administrating tranexamic acid before tourniquet inflation was studied by Tanaka et al [29] and Jansen et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies and trials have now proved the efficacy and about safety of this drug. [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14] . Earlier an intravenous (IV)dose in various doses have been used by many surgeons and their results have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier an intravenous (IV)dose in various doses have been used by many surgeons and their results have been extensively studied. [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14] Oral TXA has shown to have equal efficacy by Zohar et al [1] Nowadays, there is a increase interest in usage of intraarticular administration [2] and many others [6], [7], [8] have shown good outcome for intraarticular administration of this drug in TKA. But all of them have compared intraarticular administration of TXA with placebo controls.…”
Section: Introductionmentioning
confidence: 99%